(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The present study aimed to investigate the relationship between students’ life satisfaction and their level of adjustment. A sample of 200 students from various courses and universities in Bihar was selected using purposive and incidental sampling methods. To measure these variables, we utilized the Life Satisfaction Scale developed by Q.G. Alam and Dr. Ramji Srivastava, as well as the Revised Adjustment Inventory developed by Dr. Pramod Kumar and published by the National Psychological Corporation, Agra. The data we collected were analyzed using Pearson correlation, which revealed a significant and positive correlation between students’ life satisfaction and their level of adjustment.